2019
DOI: 10.15823/p.2019.133.6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of values and achievement motivation on teacher professionalism at Muhammadiyah 2 High School Yogyakarta, Indonesia

Abstract: Teacher professionalism is one of the important aspects of improving the academic success of students. In order to establish teacher professionalism development programs, then it needs to be identified the factors which influenced it. The research that has been around so far tend to prioritize external factors than internal factors, whereas according to a literature review, the researcher finds that internal factors have more impact on the improvement of teacher professionalism. This study aimed to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
1
17
1
1
Order By: Relevance
“…However, previous studies on this topic were mostly carried out in the fields of psychology, mental health, and logo-therapy. In fact, the literature concerning the need for the meaning of life in education has been reported by several experts, in addition it improves the teaching professionalism (Suyatno, et al 2019). According to the research conducted by Tutu (2007) and Maree (2019), the ability of teachers to discover the meaning and purpose of their lives has become an urgent need in the learning process at school.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies on this topic were mostly carried out in the fields of psychology, mental health, and logo-therapy. In fact, the literature concerning the need for the meaning of life in education has been reported by several experts, in addition it improves the teaching professionalism (Suyatno, et al 2019). According to the research conducted by Tutu (2007) and Maree (2019), the ability of teachers to discover the meaning and purpose of their lives has become an urgent need in the learning process at school.…”
Section: Introductionmentioning
confidence: 99%
“…According to the research conducted by Tutu (2007) and Maree (2019), the ability of teachers to discover the meaning and purpose of their lives has become an urgent need in the learning process at school. Suyatno et al (2019) stated that teachers with certain values tend to have an impact on the quality of teaching which important factors are that influences professionalism. Value is the crystallization of the searching process involved in the meaning of one's life (Frankl, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Kartal and Balcikanli (2019) proposed that it is important to investigate the students' readiness since it turned out that teachers can create a comfortable learning environment for the students. Improvement of the teachers' values in the learning process is necessary to create better classroom learning climate (Suyatno et al, 2019a;2019b). Good classroom climate is expected to be one of the key factors in improving the students' learning readiness.…”
Section: Discussionmentioning
confidence: 99%
“…It means that 91.6% of student learning achievement is influenced by factors other than the teacher competencies. Previous research results indicated that the factors other than the teacher competencies are students' motivation (Levpuscek & Zupancic, 2008), students' perceptions on the school environment (Gietz & McIntosh, 2014), teachers' attitudes (Levpuscek & Zupancic, 2008), values and achievement motivation (Suyatno et al, 2019), and class composition (Gottfried, 2012).…”
Section: International Journal Of Educationmentioning
confidence: 99%